Meloxicam in rheumatology practice: The history of its use in the therapy of pain - L. I. Alekseeva; P. S. Kovalenko (Современная ревматология, 2016)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used to treat pain syndrome in acute and chronic diseases of various genesis, which are accompanied by pain and inflammation. However, the use of NSAIDs is partially limited by their adverse reactions (ARs), so great attention has been recently given to the safety of NSAIDs and to the elaboration of guidelines for their administration. Therapy with NSAIDs requires that a physician should be aware of not only the mechanism of their action, but also the possible ARs, as well as their risk factors and ways of correction. It is emphasized that NSAIDs should be prescribed in terms of the possible risk of complications in different organs and tissues. The review considers the gastrointestinal, renal, and cardiac safety of NSAIDs, such as the extensively used drug meloxicam in particular. Meloxicam is as effective as nonselective NSAIDs, but due to the primary inhibition of cyclooxygenase-2, it has also a better safety profile: when it is used, there are rare gastrointestinal complications and a low cardiovascular risk that is chiefly represented by a vascular component, which makes possible to use it with caution in patients at cardiovascular risk. The results of numerous investigations show that meloxicam has a good efficacy/safety ratio and noticeable analgesic and anti-inflammatory effects, which makes it the drug of choice for the treatment of a wide range of rheumatic diseases and acute and chronic diseases of the joint and spinal column. It is pointed out that there is a need for further clinical trials of the safety of meloxicam to specify individual mechanisms of its cardiotoxicity.